From a mother's point of view: Psycho-social predictors of maternal monitoring strategy and adolescents' electronic media use. (April 2021) - Schenkel, Konstantin; Radtke, Theda; Luszczynska, Aleksandra; Lüscher, Janina; Kulis, Ewa; Scholz, Urte
Abstract: Introduction: As early adolescents have limited capacities for self-regulating electronic media use (EMU), parental monitoring is needed. However, research has shown that parents do not exert much monitoring over their children's EMU. A theory-based approach may help to identify key predictors of parental monitoring and its effects on adolescents' EMU. Applying the Health Action Process Approach (HAPA), this study examined maternal psycho-social predictors of maternal monitoring of EMU and, subsequently, children's EMU. Methods: In Switzerland, 105 mother-adolescent dyads participated in an observational study with two time points (baseline, T1, and follow-up, T2) two weeks apart. Mothers ( M age = 43.83 years, SD = 4.45) reported on their HAPA variables and their children's EMU. Adolescents ( M age = 12.13 years, SD = 0.99; 60 girls and 45 boys) also reported their EMU. Results: Maternal outcome expectancies (T1) for less EMU were positively related (β = 0.25) with their intention to monitor EMU (T1). Further, intention was positively associated (β = 0.45) with planning to monitor EMU (T1) which in turn predicted marginally (β = 0.18) maternal monitoring (T2). No significant associations were found between maternal monitoring (T2) and adolescents' EMU (T2) reported by mothers and adolescents. Conclusions: Contrary to hypotheses derived from the HAPA, findings demonstrate that not all the HAPA variables are linked to maternal monitoring of adolescents' EMU. More research is thus needed to identify antecedents and consequences of different strategies of maternal monitoring.